Mechanism understanding for stripping electrochemistry of Li metal anode. Issue 4 (31st December 2021) - Jiang, Feng‐Ni; Yang, Shi‐Jie; Liu, He; Cheng, Xin‐Bing; Liu, Lei; Xiang, Rong; Zhang, Qiang; Kaskel, Stefan; Huang, Jia‐Qi
Abstract: The pursuit of sustainable energy has a great request for advanced energy storage devices. Lithium metal batteries are regarded as a potential electrochemical storage system because of the extremely high capacity and the most negative electrochemical potential of lithium metal anode. Dead lithium formed in the stripping process significantly contributes to the low efficiency and short lifespan of rechargeable lithium metal batteries. This review displays a critical review on the current research status about the stripping electrochemistry of lithium metal anode. The significance of stripping process to a robust lithium metal anode is emphasized. The stripping models in different electrochemical scenarios are discussed. Specific attention is paid to the understanding for the electrochemical principles of atom diffusion, electrochemical reaction, ion diffusion in solid electrolyte interphase (SEI), and electron transfer with the purpose to strengthen the insights into the behavior of lithium electrode stripping. The factors affecting stripping processes and corresponding solutions are summarized and categorized as follows: surface physics, SEI, operational and external factors. This review affords fresh insights to explore the lithium anode and design robust lithium metal batteries based on the comprehensive understanding of the stripping electrochemistry. Abstract : Lithium metal batteries with theoretically high energy density are strongly considered as a potential electrochemical storage system. Dead lithium formed in the stripping process of lithium metal anode significantly hinders the practical applications. This review comprehensively summarizes the current research status about the stripping electrochemistry of lithium metal anode. The stripping models in different electrochemical scenarios are discussed. The factors affecting stripping processes and corresponding solutions are outlined. This review affords fresh insights to design robust lithium metal batteries based on the comprehensive understanding of the stripping electrochemistry.